Pengembangan Bahan Ajar PAI pada Lembaga Pendidikan Madrasah dan Pondok Pesantren dalam Era Digital - Arman Paramansyah; Faisal Abriansyah; Cut Putri Qory Ardianti; Frida Aulia; Gagan Jamaludin; Raihan Nuryasa Fartusi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research focuses on the development of teaching materials for Islamic Education (PAI) in madrasahs and Islamic boarding schools in the digital era. The development process involves analyzing needs, designing, implementing, and evaluating teaching materials that are suitable for the traditional context while integrating technology. The main objective is to enhance the relevance and effectiveness of PAI learning amidst technological advancements. The research aims to provide practical guidance for developing Islamic education materials that can be tailored to contemporary demands while preserving fundamental religious values and identity.